A comparative study on the synthesis and properties of suspension and solution precursor plasma sprayed hydroxyapatite coatings. Issue 13 (September 2017) - Aruna, S.T.; Kulkarni, Saraswati; Chakraborty, Manjusha; Kumar, S. Senthil; Balaji, N.; Mandal, Chitra
Abstract: In the present study, hydroxyapatite (HAp) coatings were deposited on Ti-6Al-4V alloy by solution precursor plasma spray (SPPS) and suspension plasma spray (SPS) processes and the properties of the coatings were compared. The feedstock powder for SPS method was prepared by coprecipitation technique and characterized for phase and morphology. The obtained HAp coatings were characterized by X-ray diffractometry, Raman spectroscopy and FT-IR spectroscopy. The biocompatibility of the coatings was evaluated using osteoblast like cells. Both the SPS and SPPS hydroxyapatite coatings exhibited similar crystallinity. Interestingly, the HAp-SPS coating showed marginally higher biocompatibility compared toHAp-SPPS and control samples. The wear and corrosion behavior of these coatings was also studied in Hanks' medium. The hydroxyapatite coating fabricated from SPS technique exhibited better corrosion and wear resistance compared to SPPS coating.